PENGARUH KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KINERJA PERAWAT DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Meyzi Heriyanto, Furqon Dasrin, Sujianto, (Jurnal Ilmu Administrasi Negara, 2020)
Leadership, Workload, Motivation and Performance of Nurses. Effect of Leadership and Workload on Nurse Performance with Motivation as an Intervening Variable in Arifin Achmad Regional Hospital in Riau Province. This study aims to see and know the direct and indirect effects of Leadership and Workload on Nurse Motivation and Performance. The population in this study were all nursing nurses who served in 22 inpatients at Arifin Achmad Regional Hospital, amounting to 487 people, the method of selecting samples in this study used the Slovin formula method so that the number of samples obtained in this study was 100 nurses. The results in this study that Leadership and Motivation have a significant positive effect on nurse performance. Workload has a significant negative effect on nurse performance. Leadership and Workload affect nurses' performance through motivation.